Fe atoms anchored on defective nitrogen doped hollow carbon spheres as efficient electrocatalysts for oxygen reduction reaction - Su, P.; Huang, W.; Zhang, J.; Guharoy, U.; Du, Q.; Sun, Q.; Jiang, Q.; Cheng, Yi; Yang, J.; Zhang, X.; Liu, Y.; Jiang, San Ping; et al. (TSINGHUA UNIV PRESS, 2021)
Defective electrocatalysts, especially for intrinsic defective carbon, have aroused a wide concern owing to high spin and charge densities. However, the designated nitrogen species favorable for creating defects by the removal of nitrogen, and the influence of defects for the coordination structure of active site and oxygen reduction reaction (ORR) activity have not been elucidated. Herein, we designed and synthesized a pair of electrocatalysts, denoted as Fe-N/C and Fe-ND/C for coordination sites of atomic iron-nitrogen and iron-nitrogen/defect configuration embedded in hollow carbon spheres, respectively, through direct pyrolysis of their corresponding hollow carbon spheres adsorbed with Fe(acac)3. The nitrogen defects were fabricated via the evaporation of pyrrolic-N on nitrogen doped hollow carbon spheres. Results of comparative experiments between Fe-N/C and Fe-ND/C reveal that Fe-ND/C shows superior ORR activity with an onset potential of 30 mV higher than that of Fe-N/C. Fe-ND sites are more favorable for the enhancement of ORR activity. Density functional theory (DFT) calculation demonstrates that Fe-ND/C with proposed coordination structure of FeN4−x (0<x<4) anchored by OH as axial ligand during ORR, weakens the strong binding of OH* intermediate and promotes the desorption of OH* as rate-determining step for ORR in alkaline electrolyte. Thus, Fe-ND/C electrocatalysts present much better ORR activity compared with that of Fe-N/C with proposed coordination structure of FeN4. [Figure not available: see fulltext.]